On the Rediscovery of Four Rare Species of Symplocos Jacq. (Symplocaceae) in the Muthukuzhivayal Region of Kanyakumari District, Tamil Nadu - Henry, A. N.; Swaminathan, M. S. (Indian Forester, 1981)
Four rare species of Symplocos Jacq. were relocated in the dense evergreen forest patches of Muthukuzhivayal region of Kanyakumari District, Tamil Nadu, S. latiflora C.B. Clarke is a new record for India; S. oligandra Bedd., S. sessilis C.B. Clarke and S. wynadense (O. Ktze.) Nooteboom are recorded after a lapse of six to ten decades.